Setting up the operation of a Science Centre using process management tools - Darnai, Balázs (Acta Agraria Debreceniensis, 2014)
Nowadays, Science Centres, which have a very long tradition in Europe, are continuously spreading in Hungary. These institutions primarily aim at raising public awareness of science in young people via informal learning (hands-on, minds-on etc.) methods. Based on this phenomenon, the construction of Scientific Adventure Park has been started in the Debrecen Botanical Garden. In addition, the Municipality of Debrecen established a new organization who will be responsible the reaching the defined goals and sustainability of Debrecen Science Centre according to the Application Form. Therefore, it will be designed a new institution with characteristics of Science Centre and provide innovative and complex services in the segments of culture and education. In this paper, I'm searching for answers to the question if based on this process-oriented method and  management approach; it is possible to design operation system capable of achieving the strategic goals mentioned above.